Hyperthyroid Heart Disease With Some Comorbidities - Hasanuddin, Abdi Dzul Ikram; Dunggio, Sandra; Zubaidi, Hannan (Fakultas Kedokteran Universitas Muslim Indonesia, 2020)
Thyroid disease is quite common. The cardiovascular clinical manifestations of hyperthyroidism are palpitation, systolic hypertension, fatigue, or with the basis of existing heart disease, angina or heart failure. In men, the disease is more frequently to develop into congestive heart failure than in women, thus more exploration is needed. This case report discussed a 42-year-old male patient who was admitted to the emergency department due to palpitations, shortness of breath aggravated with activity and lie down position, and alleviated with resting, cough with white sputum, epigastric pain, and constipation since the past 3 days. He was diagnosed with a history of hyperthyroidism and congestive heart disease 1 year ago and routinely consumed propylthiouracil (PTU). He had a history of herniotomy 10 days before admission. The patient did not have a history of hypertension, diabetes mellitus, or hypercholesterolemia. The patient has a smoking habit of up to 3 packs/day since a teenager. The patient was diagnosed with hyperthyroid heart disease (congestive heart failure, atrial fibrillation, and coronary heart disease) with comorbid of electrolyte imbalance, hypoalbuminemia, and thrombocytopenia. The patient was treated in the Intensive Care Unit (ICU) and was given oxygen therapy, crystalloid infusion, antithyroid drug, beta-blocker, diuretics, digitalis, anti-angina, anti-thrombotic, and adjunct therapy. The patient was treated for 8 days in ICU, followed by 2 days in the ward with a good outcome. Early detection and intervention followed by close monitoring is key management for the patient with hyperthyroid heart disease, especially in a male patient, to achieve a better outcome.